Reducing Musculoskeletal Disorders through the KURJAMIS Intervention: A Quasi-Experimental Study - Sumardiyono, Sumardiyono; Puspitasari, Yunita Dwi; Widyaningsih, Vitri (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2025)
Musculoskeletal disorders refer to complaints that occur in a person's muscles and skeleton, ranging from mild to severe. Sido Makmur broomstick industry is one of the broomstick industries in Boyolali. During 8 hours of work, workers in the fiber assembly section do their work by sitting. From the survey results, workers experience pain that is dominant in the waist, neck, buttocks, right calf, left calf, left thigh and right thigh. Therefore, it is necessary to improve the workstation. The purpose of this study was to determine the effect of KURJAMIS on musculoskeletal disorders in Broom Craftsmen. The research method used was quasi-experimental with a pre-test post-test approach with a control group. The research sample of 30 people was taken using total sampling. Assessment of musculoskeletal disorders using the Nordic Body Map (NBM) questionnaire, data collection was carried out 2 times, before and after using KURJAMIS. Analysis using multiple linear regression by controlling for gender, age, length of service, and RULA score. The results showed that there was a significant main effect of the time of measurement of musculoskeletal disorders (pre-test and post-test) on the score of musculoskeletal disorders (p = 0.001). This shows that there was a significant decrease in the musculoskeletal disorder score after the use of KURJAMIS. Although there was a main effect of the time of measurement of musculoskeletal disorders, the results of the analysis also showed a significant reduction in the scores of musculoskeletal disorders.